2020
DOI: 10.1021/acsaem.0c00779
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in High-Energy Commercial Li Batteries while Cycling at Standard Conditions: An In Situ Neutron Powder Diffraction Study

Abstract: Commercially available 18650 Li-ion batteries are considered for high energy density storage and usage in mobile applications as well as to store energy from intermittent energy sources. This has triggered intense research for suitable electrode and electrolyte materials, while their current stateof-the-art, temperature dependent performance is hardly described in detail. The fatigue process in two brands of rechargeable commercial high-energy Li-ion batteries (18650-type, 3500 mAh, LiNi 0.83 Mn 0.07 Co 0.11 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…46,[49][50][51] Correspondingly, commercial state of the art LIBS can least for up to two decades for stationary storage applications. 50,52,53 SIB, with a much lower technological maturity, show an even higher variability. 53 While cycle lives of experimental laboratory cells are oen comparably low, some reports state that SIB achieve between 500 until up to 2000 full cycles at a Depth of Discharge (DOD) of 80%, 54 and might reach up to 4000 cycles at 1C until 80% of initial capacity, which is compatible with current state of the art LIB.…”
Section: Use Phasementioning
confidence: 96%
“…46,[49][50][51] Correspondingly, commercial state of the art LIBS can least for up to two decades for stationary storage applications. 50,52,53 SIB, with a much lower technological maturity, show an even higher variability. 53 While cycle lives of experimental laboratory cells are oen comparably low, some reports state that SIB achieve between 500 until up to 2000 full cycles at a Depth of Discharge (DOD) of 80%, 54 and might reach up to 4000 cycles at 1C until 80% of initial capacity, which is compatible with current state of the art LIB.…”
Section: Use Phasementioning
confidence: 96%
“…Additionally, neutrons, having significantly higher penetration depth than X‐rays, can also be used to study LiBs. [ 39–47 ] Recent developments in neutron diffraction imaging techniques, such as neutron diffraction computed tomography (ND‐CT) and direct/real space neutron diffraction imaging, [ 48–51 ] have shown that neutron diffraction can be considered as a powerful characterization tool for ex situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity fade results indicate that increasing the temperature to 35 °C and 45 °C has a beneficial effect on the capacity retention, and that the charging current is at the limit of what the cells can handle. The major capacity loss is from loss of active lithium and is most likely consumed in the SEI formation as proven by in-situ neutron powder diffraction along with electrochemical analysis in our previous work 33 . Nevertheless, as this study aims to estimate the battery capacity based on data-driven methods, the relaxation process after fully charging is taken for feature extraction as the relaxation process is easily obtained in battery real use conditions.…”
Section: Data Generationmentioning
confidence: 79%